Pengaruh pelatihan asertivitas terhadap penurunan Kecemasan sosial pada siswa korban bullying - Dimas Agil Permadi; Suyanti Suyanti (PSYCOMEDIA : Jurnal Psikologi, 2022)
Social anxiety due to bullying in students can interfere with student achievement, this social anxiety makes students reluctant to interact in the school environment so they are afraid to go to school. This study aims to determine the effect of assertiveness training in reducing social anxiety of students who are victims of bullying in SMP 17 August. This training design uses a quasi-experimental pre-post test without control group design with 12 samples by purposive sampling. This study uses the Wilcoxon Signed Ranks Test with a p-value of 0.000 (p <0.05), meaning that there is an effect of assertiveness training in reducing social anxiety for students who are victims of bullying.